PENGARUH MODEL EXAMPLE NON EXAMPLE TERHADAP HASIL BELAJAR IPA SISWA KELAS V SEKOLAH DASAR - Astuti, Puji; Ermiana, Ida (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2018)
This study aims to determine the effect of Example Non Example for the science learning achievement the students grade 5th in cluster IV central Praya sub-district. The population of this study was all 5th grade students in cluster IV central Praya sub-district. Sampling was done by cluster random sampling technique, obtained by jorong elementary school students as the experimental class and dakung public elementary school as a control class. In the learning axperimental group using the Example Non Example learning model, while in the control group using a conventional learning. The research instruments in the form of multiple choice questions amounted to 26 questions. The result showed that the average value (postest) of science learning achievement the students of the experimental class using Example Non Example was 73,72. While the average value (postest) of science learning achievement the students of the control class using the conventional learning was 52,5. So, there are significant differences between the science learning achievement the students who use Example Non Example learning model by using conventional learning. Science learning achievement data were analyzed using polled variance t-test, obtained result of tcount > ttable (6,75 > 1,99) at the significance level of 5%. Based on the gain test, it can be seen that there is an increase in science learning achievement of 0,466 in the medium category of experimental students and 0,232 in the low categorized control class. So it can be concluded that there is an effect of using Example Non Example for the science learning achievement the students grade 5th in cluster iv central Praya sub-district.